Computers and Productivity How Firms Make a General Purpose Technology Work - Hempell, Thomas (ZEW Economic Studies, 2006)
Information and communication technologies (ICTs) create potentials for considerable productivity gains and for higher economic growth. However, ICTs also pose varied challenges to firms in order to benefit from these potentials. Highlighting the importance of innovations, firm-sponsored training, and recruitment of high-skilled workers, this monograph analyses why and to what extent firms differ in their capabilities to make ICT work productively. The work also comprises a detailed discussion of economic theory concerning ICT use and complementary firm strategies. In addition it provides a comprehensive treatment of various methodological issues concerning the measurement of firm-level productivity in econometric analyses. .